Developing the Supply Chain of a Manufacturing Company - Müller, Paul (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The study is conducted as a commission work for a manufacturing company in a fast-paced market environment. The study was initiated with the notion, that the case supply chain is not agile enough in responding to cliental needs. The initial issues related to increasing product portfolios, increasing amounts of stock keeping units and increasing safety stocks leading to obsolescence and inability to respond and forecast demand. The objective of the study is to clarify the current state and underlying issues followed by proposals for improvement. The main research problem was further divided into parts discussing strategy and goals, decision-making, performance measurement, continuous development, matching supply and demand, growth, communication and production development. Recent scientific discussion in performance measurement and supply and demand management were used as a theoretical framework and study foundation. Furthermore, the study was conducted as a mixed-method study in order to triangulate and get a concise and holistic insight on the case supply chain’s functioning. The data were collected mostly in semi-structured interviews and using an online survey but also from the company ERP and observations. The findings underline in numerical and verbal manner the key personnel view on shortcomings towards a best in class supply chain. Main findings show a development need of 35% considering the case supply chain compared to a reference study. The current situation could be a result of working in silos, ineffective communication, the need for strategy clarification, lack of force using performance measures in supporting strategy execution, sales and operations planning immaturity, difficult to understand rules, need for responsibilities and processes clarification among others. On the other hand the case organisation does have a clear willingness to develop. The study was concluded with several suggestions. One underlined the need for revision in strategy and goals – a nearly one-to-one connection between quick responsiveness emphasis in strategy and the supply chain success was found. Also matters such as finding mutual grounds for communication, removal of barriers in processes, refinement of sales and operations planning, continuous improvement and growth perceptions were suggested. Decision-making was suggested to be conducted with higher levels of business intelligence; as was seen in the make-or-buy study, where 10% savings occurred. While managerial implications were a primary goal, a unique case and ideas for e.g. improving communication were also discussed complementing the scientific discussion.